2013
DOI: 10.1016/j.bjid.2012.10.018
|View full text |Cite
|
Sign up to set email alerts
|

Syphilis and HIV-1 among parturient women in Salvador, Brazil: low prevalence of syphilis and high rate of loss to follow-up in HIV-infected women

Abstract: In Salvador, peripartum prevalence of syphilis and HIV-1 infection among pregnant women were low, and associated with classic risk factors for both infections. The great proportion of very late diagnosis of HIV infection, and the high rate of loss of follow-up among positive mothers and their infants are of high concern.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
5
1
1

Year Published

2014
2014
2020
2020

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 10 publications
(10 citation statements)
references
References 14 publications
3
5
1
1
Order By: Relevance
“…We detected a 2.6 higher likelihood of syphilis in parturients with a late presentation to antenatal care. This confirms previous studies in Bahia, that found a close association between late/incomplete antenatal care engagement and syphilis . The association between syphilis and late presentation to antenatal care indicates existing barriers to access health services, lack of interest, or low awareness of the importance of early pregnancy screening and monitoring …”
Section: Acknowledgementssupporting
confidence: 90%
See 2 more Smart Citations
“…We detected a 2.6 higher likelihood of syphilis in parturients with a late presentation to antenatal care. This confirms previous studies in Bahia, that found a close association between late/incomplete antenatal care engagement and syphilis . The association between syphilis and late presentation to antenatal care indicates existing barriers to access health services, lack of interest, or low awareness of the importance of early pregnancy screening and monitoring …”
Section: Acknowledgementssupporting
confidence: 90%
“…We detected a high prevalence (3.7%) of probable cases of congenital syphilis and a higher proportion of maternal syphilis with previous inadequate treatment than observed in previous published works . The rapid test was positive in 4.7% of parturients.…”
Section: Acknowledgementssupporting
confidence: 42%
See 1 more Smart Citation
“…The consistent use of condoms during intercourse was low, and 20% of the surveyed women had contact with HIV-1-positive individuals. Although drugs were not used intravenously, this variable promotes other variables of risk, including unprotected sexual relations with anal intercourse, as previously shown in other studies [12, 13]. Even with the existence of a free treatment program widely distributed across the country, a large percentage of this population was not using ART, and even worse, nearly one third of this population had never used the treatment facilities.…”
Section: Discussionmentioning
confidence: 68%
“…Esse valor foi significativamente superior ao que foi obtido com estudos realizados na mesma região em anos anteriores, em que a prevalência encontrada não alcançou o valor de 1% (NÓBREGA, 2014). Isso corrobora a hipótese de que há uma subestimação (e, adicionalmente, uma subnotificação) do número de casos de sífilis em gestantes na população soteropolitana, levantada pelos estudos de vigilância epidemiológica, realizada até o momento.…”
Section: Discussionunclassified